2006
DOI: 10.1063/1.2190721
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen release and structural changes in TiO2 films during photocatalytic oxidation

Abstract: Changes in the crystal structure and grain modifications in titanium oxide ͑TiO 2 ͒ thin films were observed during the photocatalytic oxidation of hydrocarbons. When the hydrocarbon and collodion films were irradiated, single crystalline titanium oxide transformed into polycrystals. The titanium oxide films gradually became network aggregates. These changes were analyzed with a dedicated in situ transmission electron microscope and observed three dimensionally by electron tomography. A detailed analysis of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…1(b) is a HRTEM image of a film. The lattice fringes showed an interplanar spacing of 0.32 nm, which corresponded to the (110) planes of rutile TiO 2 structure [17]. The present films prepared by PLD were quite homogeneous, which mainly comprised of rutile type titanium dioxide crystallites.…”
Section: Methodsmentioning
confidence: 96%
“…1(b) is a HRTEM image of a film. The lattice fringes showed an interplanar spacing of 0.32 nm, which corresponded to the (110) planes of rutile TiO 2 structure [17]. The present films prepared by PLD were quite homogeneous, which mainly comprised of rutile type titanium dioxide crystallites.…”
Section: Methodsmentioning
confidence: 96%
“…TiO 2 films are being extensively studied because of their interesting chemical, electrical and optical properties resulting in widespread applications, e.g., in catalysis, photocatalysis, dye-sensitized photovoltaic cells, gas sensors [6][7][8][9] and pharmaceuticals [10][11][12]. Besides, TiO 2 nanofilms are widely used as protective layers for very large-scale integrated (VLSI) circuits and as antireflective (AR) coatings for optical elements and planar waveguides.…”
Section: Methodsmentioning
confidence: 99%
“…The Au and Ag nanoparticles on TiO 2 are well known as high active oxidation catalysts, and much 3D research of these catalysts has been reported [26][27][28]. HAADF-STEM tomography has proven to be a quite effective tool for analyzing such catalytic nanomaterials [29][30][31].…”
Section: Article In Pressmentioning
confidence: 99%